PERJANJIAN PINJAM MEMINJAM UANG PADA KOPERASI SIMPAN PINJAM “PURI SEDANA” DI DESA PENINJOAN PEGUYANGAN KANGIN DENPASAR - Bagus Surya Kusuma, I Gusti Ngurah; Dharma kusuma, AA Gede Agung; Dewi Kasih, Desak Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013)
Most of the Indonesian community living and residing in rural areas, where theneed for a forum to foster the ability of rural communities for the realization ofeconomic democracy that based on kinship, the cooperative is the mostappropriate corporate structure for the economy developed as a joint effort basedon the principle of kinship them. Cooperative is an association or organization ofthe economy consists of people or agencies that provide freedom in and out as amember under the existing regulations by working together in a family running abusiness, with the aim of enhancing the physical well-being of its members. Inagreement borrowing money at Puri Sedana Credit Unions, if the borrower doesnot repay the loan on time will be a default. Default is not met or neglect of dutyas defined in the agreement made between the creditor and debtor.The issue in the writing of this paper was about how the legal consequences ofdefault in the loan agreement to borrow money at Puri Sedana Credit Unions andhow the settlement pursued defaults Credit Unions Sedana Puri. Researchmethods used in preparing this paper is empirical juridical, with a studyevaluating the written law to the facts that exist in the field.legal consequences of default in the loan agreement to borrow money at PuriSedana Cooperative is a debtor is required to make restitution that has beensuffered by the cooperative, the debtor is also required to pay the loan if it can stillbe done in accordance with the warning of the cooperative, and the risk ofswitching on loan borrowers since no nonpayment in accordance with apredetermined time period. Completion of defaults by borrowers on CooperativePuri Sedana do with the settlement of non-litigation (deliberation), a non litigationis done by consultation, negotiation, mediation, conciliation or expert assessment.
Keywords: cooperative, agreements, borrowing, default